Photocatalyst coating, photocatalyst coated body, and photocatalyst coating method

JP2025023673APending Publication Date: 2025-02-17SHARP KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023128013
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

Smart Images

  • Figure 2025023673000001_ABST
    Figure 2025023673000001_ABST
Patent Text Reader

Abstract

To provide a photocatalyst coating capable of forming a photocatalyst layer having excellent water resistance and durability while maintaining photocatalytic activities.SOLUTION: A photocatalyst coating of the present disclosure comprises at least: photocatalyst particles containing tungsten oxide; a first binder; and water, wherein the first binder is 1,2-bis(trihydroxysilyl)alkane represented by the chemical formula: (HO)3Si-(CH2)n-Si(OH)3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocatalytic paint, a photocatalytic coated body, and a photocatalytic coating method. [Background technology]

[0002] Photocatalyst particles are particles that have photocatalytic activity that occurs when exposed to light. By utilizing the photocatalytic activity, it is possible to, for example, decompose harmful substances in the air, decompose substances that cause bad odors, decompose pollutants dissolved or dispersed in water, decompose fungi, inhibit fungal growth, inhibit dirt on exterior walls, or inhibit dirt on windows. In order to utilize the photocatalytic activity, it is necessary to fix the photocatalytic particles to the substrate. For example, Patent Document 1 discloses an antifouling acrylic plate consisting of an acrylic substrate, a silica layer formed on the surface of the acrylic substrate, and a photocatalytic layer formed on the silica layer. A bonding layer made of a silane coupling agent is provided between the surface of the acrylic substrate and the silica layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2011 / 059101 Summary of the Invention [Problem to be solved by the invention]

[0004] However, in the acrylic plate disclosed in Patent Document 1, the substrate and the silica layer are merely bonded together by a silane coupling agent, and this is insufficient in terms of improving the water resistance and durability of the photocatalyst layer. The present invention has been made in view of such problems, and provides a photocatalytic coating material capable of forming a photocatalytic layer having excellent water resistance and durability while maintaining photocatalytic activity. [Means for solving the problem]

[0005] The present invention includes at least a photocatalyst particle containing tungsten oxide, a first binder, and water, and the first binder has a chemical formula: (HO)3Si-(CH2) n The photocatalytic coating material is a 1,2-bis(trihydroxysilyl)alkane represented by the formula --Si(OH)3. Effect of the Invention

[0006] By using the photocatalytic coating material of the present invention, it is possible to form a photocatalytic layer that is excellent in water resistance and durability while maintaining photocatalytic activity. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is an explanatory diagram of a method for producing a photocatalyst-coated body using a photocatalyst paint according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The photocatalytic coating material of the present invention contains at least photocatalytic particles containing tungsten oxide, a first binder, and water. The first binder is represented by the chemical formula: (HO)3Si-(CH2) n It is characterized by being a 1,2-bis(trihydroxysilyl)alkane represented by the formula --Si(OH)3.

[0009] The content of the photocatalyst particles is preferably 50% by mass or more and 99% by mass or less, when the mass of the total solid content contained in the photocatalyst coating material is taken as 100% by mass. The content of the first binder is preferably 1% by mass or more and 50% by mass or less, when the mass of the total solid content contained in the photocatalytic coating material is taken as 100% by mass. The first binder is preferably a 1,2-bis(trihydroxysilyl)alkane having a carbon atom number n of 2-8. The photocatalytic coating material of the present invention preferably further contains a second binder, and the second binder is preferably a compound containing a hydroxysilyl group. The second binder is preferably a compound containing a methacryloxy group.

[0010] The total content of the first binder and the second binder is preferably 1% by mass or more and 50% by mass or less, when the mass of the total solid content contained in the photocatalytic coating material is taken as 100% by mass. The photocatalytic paint of the present invention preferably further contains a preservative component, and the preservative component is preferably ethanol. When the photocatalytic paint contains ethanol, the preservative effect of the paint can be enhanced. The photocatalytic coating material is preferably a suspension containing a first binder, the photocatalytic particles, and water.

[0011] The present invention also provides a photocatalyst-coated body comprising a substrate and a photocatalyst layer provided on the substrate. The photocatalyst layer included in the photocatalyst-coated body comprises photocatalyst particles and a photocatalyst having the chemical formula: (HO)3Si-(CH2) n and a siloxane compound containing a dehydration condensate of 1,2-bis(trihydroxysilyl)alkane represented by the formula --Si(OH)3. The present invention also provides a photocatalytic coating method comprising the steps of applying the photocatalytic coating material of the present invention onto a substrate to form a coating layer, and drying the coating layer.

[0012] The present invention will be described in more detail below with reference to a number of embodiments. The configurations shown in the drawings and the following description are merely examples, and the scope of the present invention is not limited to those shown in the drawings and the following description.

[0013] <First embodiment: Photocatalytic paint> FIG. 1 is an explanatory diagram of a method for producing a photocatalyst-coated body using the photocatalyst paint of this embodiment. The first embodiment of the present invention relates to a photocatalytic paint 2 (hereinafter, sometimes referred to as "paint 2"). The photocatalytic coating material 2 of this embodiment contains at least photocatalytic particles containing tungsten oxide, a first binder, and water. The first binder is represented by the chemical formula: (HO)3Si-(CH2) nIt is 1,2-bis(trihydroxysilyl)alkane represented by -Si(OH)3. The photocatalytic coating material 2 may be a suspension containing the first binder, photocatalytic particles, and water. The photocatalytic layer 5 can be formed by applying the photocatalytic coating material 2 of this embodiment to a substrate 3 and drying the applied layer 4.

[0014] The paint 2 may further contain a preservative component as necessary. The paint 2 of the first embodiment is a water-based paint containing water. The solvent (or dispersion medium) of the paint 2 is water, a mixture of water and ethanol, or the like. This reduces the environmental load and improves the working environment.

[0015] The binder (including the first binder) contained in the photocatalytic paint 2 becomes a siloxane compound (binder) in the photocatalytic layer 5, and bonds the substrate 3 to which the paint 2 is applied and the photocatalytic particles mainly composed of tungsten oxide. The siloxane compound (binder) also bonds the multiple photocatalytic particles contained in the photocatalytic layer 5. The paint 2 may contain one type of binder (e.g., containing only the first binder) or multiple types of binders (e.g., containing the first binder and the second binder). The paint 2 contains 1,2-bis(trihydroxysilyl)alkane (chemical formula: (HO)3Si-(CH2) n The 1,2-bis(trihydroxysilyl)alkane contained in the paint 2 may be bonded to the photocatalyst particles by a dehydration condensation reaction. In addition, multiple 1,2-bis(trihydroxysilyl)alkanes contained in the paint 2 may be bonded to the photocatalyst particles by a dehydration condensation reaction.

[0016] 1,2-Bis(trihydroxysilyl)alkanes have an alkane backbone structure (CH2) between two silicon atoms. n Each silicon atom has three hydroxyl groups (OH) bonded to it. This compound is a 1,2-bis(trialkoxysilyl)alkane (chemical formula: (C m H 2m+1 O)3Si-(CH2) n -Si(OC m H 2m+1The number of carbon atoms, n, is preferably 2 to 8. m H 2m+1 For example, the alkoxy group (C2H5O-) is an ethoxy group (C2H5O-), which becomes a hydroxyl group (-OH) through a hydrolysis reaction. Examples of alkane skeleton structures contained in 1,2-bis(trihydroxysilyl)alkane include ethane-(CH2)2-, hexane-(CH2)6-, and octane-(CH2)8-.

[0017] When the paint 2 contains 1,2-bis(trihydroxysilyl)alkane as the first binder, the following first to fourth advantages are obtained. First, the first advantage will be described. When the coating material 2 is applied to the substrate 3 and the coating layer 4 is dried, a part of the silanol group (SiOH) of the first binder and the hydroxyl group (OH) on the surface of the substrate 3 undergo dehydration condensation to form a covalent bond between the first binder (or its dehydration condensate) and the substrate 3. Also, a part of the silanol group (SiOH) of the first binder (or its dehydration condensate) and the hydroxyl group (OH) on the surface of the photocatalyst particles mainly composed of tungsten oxide undergo dehydration condensation to form a covalent bond between the first binder (or its dehydration condensate) and the photocatalyst particles mainly composed of tungsten oxide. By causing these dehydration condensation reactions, when the coating material 2 is applied to the substrate 3 and the coating layer 4 is dried, the photocatalyst particles mainly composed of tungsten oxide can be firmly bonded to the substrate 3 via the siloxane compound containing the dehydration condensate of 1,2-bis(trihydroxysilyl)alkane. By bonding firmly, the water resistance and durability of the photocatalyst layer 5 formed using the paint 2 can be improved.

[0018] 1,2-bis(trihydroxysilyl)alkane easily bonds to metal and metal oxide particles, as well as to substrates 3 such as metals, metal oxides, glass, and plastics, and can firmly bond the photocatalyst particles to the surfaces of various substrates. Therefore, the amount of binder required to form a film is smaller than the amount of photocatalyst particles, and the photocatalytic function of the photocatalyst particles is not impaired.

[0019] Next, the second advantage will be described. When the coating material 2 is applied to the substrate 3 and the coating layer 4 is dried, some of the silanol groups of the 1,2-bis(trihydroxysilyl)alkanes undergo dehydration condensation with each other, so that the 1,2-bis(trihydroxysilyl)alkanes bond to each other to generate a siloxane compound. In this way, the 1,2-bis(trihydroxysilyl)alkanes bond to each other to generate a siloxane compound, so that when the coating material 2 is applied to the substrate 3 and the coating layer 4 is dried, the photocatalyst particles mainly composed of tungsten oxide and the substrate 3 can be bonded more firmly via the siloxane compound, which is a binder. By bonding firmly, the water resistance and durability of the photocatalyst layer 5 formed using the coating material 2 can be improved.

[0020] Next, we will explain the third advantage. 1,2-bis(trihydroxysilyl)alkane has six hydroxy groups in one molecule, which gives it a high affinity for water. This high affinity for water makes it easy to incorporate into water-based paints that contain water.

[0021] Next, the fourth advantage will be described. In general, when the coating material 2 is applied to the substrate 3 and the coating layer 4 is dried, a dehydration condensation reaction occurs between the 1,2-bis(trihydroxysilyl)alkane, the substrate 3, and the photocatalyst particles mainly composed of tungsten oxide. This makes it possible to shorten the time required to manufacture the photocatalyst-coated body 10 described later in the third embodiment.

[0022] 1,2-Bis(trihydroxysilyl)alkane (chemical formula: (HO)3Si-(CH2) n -Si(OH)3) is a 1,2-bis(trialkoxysilyl)alkane (chemical formula: (RO)3Si-(CH2) n It can be obtained by hydrolyzing -Si(OR)3, R=CH3, CH2CH3, etc. in an acidic solvent to eliminate the alcohol. 1,2-bis(trialkoxysilyl)alkanes are not water-soluble, but the hydrolyzate is water-soluble, so whether or not hydrolysis has finished can be confirmed visually.

[0023] The alkane skeleton structure of the 1,2-bis(trihydroxysilyl)alkane or 1,2-bis(trialkoxysilyl)alkane is preferably an ethylene group (-(CH2)2-), a hexamethylene group (-(CH2)6-), or an octamethylene group (-(CH2)8-), of which an ethylene group is more preferred because it is more water-soluble. The alkoxy group represented by RO in the 1,2-bis(trialkoxysilyl)alkane is preferably an alkoxy group having 1 to 6 carbon atoms, more preferably an alkoxy group having 1 to 3 carbon atoms, and even more preferably a methoxy group or an ethoxy group.

[0024] The coating material 2 may contain, as a second binder, a compound containing a hydroxysilyl group different from that of the first binder, together with the 1,2-bis(trihydroxysilyl)alkane (first binder) in order to enhance adhesion. By including the second hydroxysilyl group-containing binder (second binder) in the coating material 2, the binder (siloxane compound), the photocatalyst, and the substrate 3 can be bonded more firmly in a three-dimensional manner in the photocatalyst layer 5 of the photocatalyst-coated body 10, and the adhesion of the photocatalyst layer 5 to the substrate 3 can be enhanced. The compound having a hydroxysilyl group, which is the second binder, preferably contains a methacryloxy group. Since the second binder has a hydroxysilyl group, when the coating layer 4 formed by applying the coating material 2 to the substrate 3 dries, the second binder participates in a dehydration condensation reaction together with the first binder, and a siloxane compound (binder) containing a dehydration condensation product of the first binder and a dehydration condensation product of the second binder is formed.

[0025] Examples of the second binder include vinyl-based vinyltrihydroxysilane, 3-aminopropyltrihydroxysilane, 3-glycidoxypropyltrihydroxysilane, 3-methacryloxypropyltrihydroxysilane, and 3-mercaptopropyltrihydroxysilane. The second binder contained in the paint 2 may be bonded to the photocatalyst particles by a dehydration condensation reaction. Also, a plurality of second binders contained in the paint 2 may be bonded to each other by a dehydration condensation reaction. Also, the second binder contained in the paint 2 may be bonded to the first binder (1,2-bis(trihydroxysilyl)alkane) by a dehydration condensation reaction. The ratio (B / A) of the mass (B) of the second binder to the mass (A) of the first binder contained in the paint 2 can be set to be not less than (20 / 80) and not more than (80 / 20).

[0026] In order to improve the water resistance and durability of the photocatalyst layer 5 while maintaining the photocatalytic activity of the photocatalyst layer 5, the content of the binder component (which may include a second binder) including 1,2-bis(trihydroxysilyl)alkane (first binder) in the coating material 2 is preferably 1% by mass or more and 50% by mass or less, when the mass of the total solid content contained in the coating material 2 is taken as 100% by mass. The total solid content contained in the coating material 2 is the components contained in the coating material 2 excluding the dispersion medium and the solvent (for example, water, ethanol, etc.).

[0027] In order to improve the water resistance and durability of the photocatalyst layer 5 while particularly improving the photocatalytic activity of the photocatalyst layer 5, it is more preferable that the content of the binder component (which may include a second binder) containing 1,2-bis(trihydroxysilyl)alkane (first binder) in the paint 2 is 1.0 mass% or more and 20 mass% or less when the mass of the total solid content contained in the paint 2 is 100 mass%. The binder component containing 1,2-bis(trihydroxysilyl)alkane or a dehydration condensate thereof dehydrates and condenses with the photocatalyst particles mainly containing tungsten oxide, and the binder component containing 1,2-bis(trihydroxysilyl)alkane or a dehydration condensate thereof dehydrates and condenses with the substrate 3, so that the photocatalyst particles mainly containing tungsten oxide and the substrate 3 are strongly bonded by covalent bonds via the siloxane compound containing the dehydration condensate of 1,2-bis(trihydroxysilyl)alkane. Therefore, even if the content of the binder component containing 1,2-bis(trihydroxysilyl)alkane in the paint 2 is low, the photocatalyst particles mainly composed of tungsten oxide and the substrate 3 are strongly bonded via the siloxane compound (binder). Therefore, the amount of 1,2-bis(trihydroxysilyl)alkane, which is the binder in the paint 2, added can be reduced. This makes it possible to suppress the photocatalytic activity of the photocatalyst layer 5 from being impaired by the siloxane compound, which is the binder, and to suppress the embedding of the photocatalyst particles in the siloxane compound, which is the binder. As a result, the photocatalytic activity of the photocatalyst layer 5 can be particularly improved while improving the water resistance and durability of the photocatalyst layer 5.

[0028] (Photocatalytic particles mainly composed of tungsten oxide) Photocatalyst particles mainly composed of tungsten oxide have photocatalytic activity in the short wavelength region of visible light. In detail, when the photocatalyst particles are irradiated with light having an energy equal to or greater than the energy gap between the valence band and the conduction band, electrons in the valence band of the photocatalyst particles are excited to the conduction band, generating holes in the valence band. These electrons and holes move inside the photocatalyst particles. The electrons reduce oxygen, generating superoxide anions. The holes oxidize water, generating hydroxyl radicals. The generated hydroxyl radicals generate active oxygen species. The generated active oxygen species achieve, for example, the decomposition of harmful substances, antibacterial properties, and antifouling properties.

[0029] The tungsten oxide is not particularly limited, and commercially available products can be used as appropriate. Examples of tungsten oxide include WO3 (tungsten trioxide), WO2, WO, W2O3, W4O5, and W4O. 11 , W 25 O 73 , W 20 O 58 , and W 24 O 68 , and mixtures thereof. In order to improve the photocatalytic activity of the photocatalytic layer 5, the tungsten oxide is preferably WO3. A part of the tungsten oxide may be reduced to a V valence. However, it is preferable to use the tungsten oxide after oxidizing it to a VI valence. As a method for oxidizing to a VI valence, for example, a method of baking tungsten oxide at a high temperature can be mentioned. The crystal structure of the tungsten oxide is not particularly limited.

[0030] The average particle size of the photocatalyst particles mainly composed of tungsten oxide is preferably 5 nm or more and 200 nm or less. This makes the photocatalyst particles less likely to aggregate and easier to redisperse. If the average particle size of the photocatalyst particles is 200 nm or less, there is a tendency for the particles to be mixed uniformly with other paint components, and the photocatalyst particles can be prevented from detaching from the photocatalyst layer 5 formed by the paint 2. The average particle size is calculated based on the specific surface area (unit: m) of the particles measured by the BET method. 2 / g) assuming that the primary particles are spherical.

[0031] The photocatalyst particles mainly composed of tungsten oxide may have co-catalyst particles on the surface. The co-catalyst particles are preferably metal particles, more preferably transition metal particles, and even more preferably platinum group metal particles. Examples of platinum group metal particles include particles of Pt, Pd, Rh, Ru, Os, and Ir. By providing the co-catalyst particles on the surface of the tungsten oxide particles, the energy gap between the valence band and the conduction band of the tungsten oxide particles can be reduced, and the photoresponse in the visible light region can be improved.

[0032] The content of the photocatalyst particles mainly composed of tungsten oxide in the paint 2 is preferably 50% by mass or more and 99% by mass or less, and more preferably 20% by mass or more and 99% by mass or less, when the mass of the total solid content contained in the paint 2 is 100% by mass. When the coating layer 4 dries, the 1,2-bis(trihydroxysilyl)alkane or its dehydration condensate dehydrates and condenses with the photocatalyst particles, and the 1,2-bis(trihydroxysilyl)alkane or its dehydration condensate dehydrates and condenses with the substrate 3, so that the photocatalyst particles and the substrate 3 are strongly bonded via the siloxane compound (binder) containing the dehydration condensate of the 1,2-bis(trihydroxysilyl)alkane. Therefore, even when the content of the photocatalyst particles in the photocatalyst layer 5 is high, in other words, when the content of the binder is low, the photocatalyst particles and the substrate 3 are strongly bonded via the binder (siloxane compound). This allows a reduction in the amount of 1,2-bis(trihydroxysilyl)alkane added as a binder to the coating material 2. This prevents the photocatalytic activity of the photocatalyst layer 5 from being impaired by the siloxane compound (binder), and also prevents the photocatalytic particles from being embedded in the siloxane compound (binder). As a result, the photocatalytic activity of the photocatalyst layer 5 can be particularly improved while improving the water resistance and durability of the photocatalyst layer 5.

[0033] (Preservative ingredients) The paint 2 preferably further contains a preservative component in addition to the photocatalyst particles mainly composed of tungsten oxide, the binder, and water. The preservative component may be ethanol, an alkanediol having 3 to 6 carbon atoms (e.g., 1,3-propanediol, 1,2-pentanediol, 1,2-hexanediol, 4-oxa-2,6-heptanediol), or a water-soluble copper compound (e.g., copper gluconate, copper sulfate, copper chloride, copper nitrate, copper acetate, copper lactate, copper butyrate, etc.), or a water-soluble silver compound (e.g., silver nitrate, silver oxide, silver sulfate, silver chloride, silver sulfite, silver carbonate, silver acetate, silver lactate, etc.).

[0034] <Second embodiment: Paint manufacturing method> The second embodiment of the present invention relates to a method for producing paint 2. The paint 2 produced by the production method of the second embodiment is the paint 2 of the first embodiment. The photocatalyst layer 5 formed using the paint 2 produced by the production method of the second embodiment is excellent in water resistance and durability while maintaining photocatalytic activity for the same reasons as described in the first embodiment. The production method of paint 2 of the second embodiment includes, for example, a paint preparation step.

[0035] (Paint preparation process) In the paint preparation step, a binder (which may contain a second binder) containing 1,2-bis(trihydroxysilyl)alkane (first binder), photocatalyst particles mainly composed of tungsten oxide, and water are mixed to obtain the paint 2 of the first embodiment. In order to improve dispersibility, it is preferable to mix 1,2-bis(trihydroxysilyl)alkane with the photocatalyst particles mainly composed of tungsten oxide. The photocatalyst particles mainly composed of tungsten oxide may be added in the form of a photocatalyst liquid containing photocatalyst particles and a dispersion medium.

[0036] In addition, the binder containing 1,2-bis(trihydroxysilyl)alkane may be obtained by mixing the binder liquid containing 1,2-bis(trialkoxysilyl)alkane and a solvent with photocatalyst particles mainly composed of tungsten oxide, which is acidic, or a dispersion liquid of photocatalyst particles mainly composed of tungsten oxide, to hydrolyze the alkoxy group. Examples of the dispersion medium contained in the dispersion liquid of the photocatalyst particles include polar solvents, more specifically, water and ethanol. Examples of the solvent and dispersion medium contained in the binder liquid include polar solvents, more specifically, water, methanol, ethanol, and propanol.

[0037] <Third embodiment: Photocatalyst-coated body and its manufacturing method> A third embodiment of the present invention relates to a photocatalyst-coated body and a manufacturing method thereof. The photocatalyst-coated body 10 includes a substrate 3 and a photocatalyst layer 5 provided on the substrate 3. The photocatalyst layer 5 includes photocatalyst particles and a photocatalyst having the chemical formula: (HO)3Si-(CH2) n and a siloxane compound containing a dehydration condensate of 1,2-bis(trihydroxysilyl)alkane (first binder) represented by the formula -Si(OH). The siloxane compound may contain a dehydration condensate of the second binder.

[0038] Examples of materials for the substrate 3 (specifically, the support) include glass, plastic, metal, ceramics, wood, stone, cement, concrete, fiber, fabric, paper, and leather, as well as combinations thereof. The substrate 3 may be a laminate having a plurality of layers of different materials. The material for the substrate 3 may be a material having a hydroxyl group on its surface. The paint 2 of the first embodiment contains 1,2-bis(trihydroxysilyl)alkane as the first binder. Therefore, when the substrate 3 is made of such a material, the 1,2-bis(trihydroxysilyl)alkane or its dehydration condensate undergoes dehydration condensation with the substrate 3, and the 1,2-bis(trihydroxysilyl)alkane or its dehydration condensate undergoes dehydration condensation with the photocatalyst particles. The covalent bond formed by these dehydration condensations firmly bonds the photocatalyst particles and the substrate 3 via the binder (siloxane compound).

[0039] The photocatalyst layer 5 included in the photocatalyst-coated body 10 can be manufactured using the paint 2 of the first embodiment. Because the paint 2 of the first embodiment is used, for the same reasons as described in the first embodiment, the photocatalyst layer 5 included in the photocatalyst-coated body 10 manufactured by the manufacturing method of the third embodiment has excellent water resistance and durability while maintaining photocatalytic activity.

[0040] The photocatalyst layer 5 is provided on the substrate 3. The photocatalyst layer 5 may be disposed directly on the substrate 3. Alternatively, the photocatalyst layer 5 may be disposed on the substrate 3 via a primer layer. The primer layer is formed by an undercoating agent. The photocatalyst layer 5 is made of photocatalyst particles and a compound represented by the chemical formula: (HO)3Si-(CH2) n and a siloxane compound containing a dehydration condensate of 1,2-bis(trihydroxysilyl)alkane (first binder) represented by -Si(OH)3. The siloxane compound is a compound having a siloxane bond and containing a dehydration condensate of the first binder. The siloxane compound may be a compound containing a dehydration condensate of the first binder and the above-mentioned dehydration condensate of the second binder.

[0041] A manufacturing method for the photocatalyst-coated body 10 of the third embodiment includes, for example, a photocatalyst layer forming step. (Photocatalyst layer formation process) In the photocatalyst layer forming step, the paint 2 of the first embodiment is applied onto the substrate 3, and the coating layer 4 is dried. This bonds the photocatalyst particles to the substrate 3 via the siloxane compound (binder) containing the dehydration condensate of 1,2-bis(trihydroxysilyl)alkane. At least a part of the water contained in the coating layer 4 is removed by drying the coating layer 4. In this manner, a photocatalyst layer 5 containing the photocatalyst particles and the siloxane compound (binder) containing the dehydration condensate of 1,2-bis(trihydroxysilyl)alkane is formed on the substrate 3. Since the paint 2 of the first embodiment contains the binder containing 1,2-bis(trihydroxysilyl)alkane, the photocatalyst layer 5 can be formed without performing a hydrolysis treatment in the photocatalyst layer forming step.

[0042] The paint 2 of the first embodiment contains a binder containing 1,2-bis(trihydroxysilyl)alkane. By drying the paint 2 (coating layer 4), the 1,2-bis(trihydroxysilyl)alkane or its dehydration condensate and the photocatalyst particles undergo dehydration condensation, and the 1,2-bis(trihydroxysilyl)alkane or its dehydration condensate and the substrate 3 undergo dehydration condensation to generate a siloxane compound. The photocatalyst particles and the substrate 3 are firmly bonded to each other via the binder (siloxane compound) by the covalent bond formed by these dehydration condensations. The strong bond can improve the water resistance and durability of the photocatalyst-coated body 10 including the photocatalyst layer 5 formed by the paint 2 of the first embodiment. Because of its excellent water resistance and durability, the photocatalyst-coated body 10 manufactured by the manufacturing method of the third embodiment can exhibit photocatalytic activity in any environment, such as indoors, outdoors, in the air, and in water.

[0043] The method of applying the coating material 2 onto the substrate 3 is not particularly limited. Examples of the method of applying the coating material 2 onto the substrate 3 include spin coating, dipping, spraying, roll coating, gravure, wire bar, air knife, and inkjet. The coating material 2 may be applied to at least a part of the substrate 3. The thickness of the photocatalyst layer 5 to be formed is not particularly limited. Regardless of the thickness of the photocatalyst layer 5 obtained by any application method, the effect of the coating material 2 of the first embodiment can be obtained.

[0044] There is no particular limitation on the method for drying the coating material 2 (coating layer 4) applied onto the substrate 3. Examples of methods for drying the coating material 2 (coating layer 4) applied onto the substrate 3 include room temperature drying, ventilation drying, forced drying using a dryer, and baking. The temperature for drying the coating material 2 (coating layer 4) applied onto the substrate 3 is preferably 20°C or higher and 150°C or lower.

[0045] Before applying the coating material 2 onto the substrate 3, it is preferable to modify the surface of the substrate 3 to be hydrophilic. By modifying the surface of the substrate 3 to be hydrophilic, the wettability of the coating material 2 to the substrate 3 can be improved, and a photocatalyst layer 5 having a more uniform thickness can be formed.

[0046] Examples of methods for modifying the surface of the substrate 3 to be hydrophilic include chemical treatment, mechanical treatment, corona treatment, flame treatment, ultraviolet irradiation treatment, high frequency treatment, glow discharge treatment, plasma treatment, laser treatment, mixed acid treatment, and ozone oxidation treatment. Another example of a method for modifying the surface of the substrate 3 to be hydrophilic includes a method of applying an undercoat agent onto the substrate 3 to form a primer layer on the substrate 3. Among these methods, plasma treatment, ultraviolet irradiation treatment, corona treatment, or glow discharge treatment is preferred, and ultraviolet irradiation treatment is more preferred.

[0047] An example of ultraviolet irradiation treatment will be described. The surface of the substrate 3 is irradiated with ultraviolet rays using an ultraviolet ray irradiating device. In this way, before the coating material 2 is applied onto the substrate 3, the surface of the substrate 3 is irradiated with ultraviolet rays to modify the surface of the substrate 3 to be hydrophilic. Since it is easy to modify the surface of the substrate 3 to be hydrophilic, the wavelength of the ultraviolet rays is preferably 150 nm or more and 350 nm or less, and more preferably 200 nm or more and 300 nm or less. The device for irradiating ultraviolet rays is not particularly limited, and a known device can be used as appropriate. Examples of the source of ultraviolet rays include a low-pressure mercury lamp and an excimer lamp. The wavelength (λ) of the ultraviolet rays irradiated from the low-pressure mercury lamp is, for example, 254 nm and 185 nm. The wavelength (λ) of the ultraviolet light irradiated from the excimer lamp is, for example, at least one of 308 nm (XeCl* lamp), 227 nm (KrCl* lamp), 172 nm (Xe2* lamp), 126 nm (Ar2* lamp), and 146 nm (Kr2* lamp). The time for irradiating the ultraviolet light varies depending on the irradiance and irradiation conditions, but is, for example, from 1 minute to 1 hour.

[0048] <Preparation of photocatalytic paint> Photocatalytic coating materials A-1 to A-9 and B-1 to B-4, the compositions of which are shown in Table 1, were prepared.

[0049] [Table 1]

[0050] "20wt% photocatalyst dispersion" in Table 1 indicates a suspension (dispersion medium: water) containing 20wt% platinum-loaded tungsten oxide particles. The 20wt% photocatalyst dispersion was prepared by the following method. Specifically, 200g of tungsten oxide (Kishida Chemical Co., Ltd.) was mixed with 1000mL of pure water, and then dispersed under ultrasonic irradiation to obtain dispersion A of tungsten oxide particles. Hexachloroplatinum(VI) hexahydrate (Kishida Chemical Co., Ltd., purity 98.5%) was dissolved in dispersion A to obtain dispersion B of tungsten oxide particles. The amount of hexachloroplatinum(VI) hexahydrate added was such that the ratio of the mass of platinum alone to the mass of the tungsten oxide particles was 0.05% by mass. Dispersion B was heated at 100°C to evaporate the water and bake, obtaining 0.05wt% platinum-loaded tungsten oxide particles. Then, pure water was added to the 0.05 wt% platinum-loaded tungsten oxide particles so that the ratio of the 0.05 wt% platinum-loaded tungsten oxide particles was 20 mass % to prepare a 20 wt% photocatalyst dispersion. The average particle diameter of the 0.05 wt% platinum-loaded tungsten oxide particles in the 20 wt% photocatalyst dispersion was 175 nm. Table 1 also shows the mass of the photocatalyst solid content and the mass of water contained in the 20 wt% photocatalyst dispersion. The photocatalyst solid content is the solid content remaining when the 20 wt% photocatalyst dispersion is dried at 100 ° C.

[0051] The binders contained in the photocatalytic paints were binders (1) to (4). The binders contained in each photocatalytic paint are shown in Table 1. Photocatalytic paint B-1 does not contain a binder. The binder (1) is 1,2-bis(triethoxysilyl)ethane, a raw material for 1,2-bis(trihydroxysilyl)ethane. When 1,2-bis(triethoxysilyl)ethane is mixed with a photocatalyst dispersion liquid and pure water, it is hydrolyzed into 1,2-bis(trihydroxysilyl)ethane because the mixture is acidic.

[0052] The binder (2) is 1,2-bis(trimethoxysilyl)hexane, which is the raw material for 1,2-bis(trihydroxysilyl)hexane. When 1,2-bis(trimethoxysilyl)hexane is mixed with the photocatalyst dispersion liquid and pure water, it is hydrolyzed into 1,2-bis(trihydroxysilyl)hexane because the mixture is acidic. The binder (3) is 1,2-bis(trimethoxysilyl)octane, the raw material of 1,2-bis(trihydroxysilyl)octane. When 1,2-bis(trimethoxysilyl)octane is mixed with the photocatalyst dispersion liquid and pure water, it is hydrolyzed into 1,2-bis(trihydroxysilyl)octane because the mixture is acidic.

[0053] The binder (4) is 3-methacryloxypropyltriethoxysilane, a raw material for 3-methacryloxypropyltrihydroxysilane. When 3-methacryloxypropyltriethoxysilane is mixed with a photocatalyst dispersion liquid and pure water, it is hydrolyzed into 3-methacryloxypropyltrihydroxysilane because the mixture is acidic.

[0054] In Table 1, "-" indicates that the paint does not contain the corresponding material. "Total solids / paint" in Table 1 is the mass ratio of the total solids to the mass of the photocatalytic paint. The total solids is the solids remaining when the photocatalytic paint is dried at 100°C. "Binder / total solids" in Table 1 is the ratio of the mass of the binder to the mass of the total solids contained in the photocatalytic paint. "Photocatalyst / total solids" in Table 1 is the mass ratio of photocatalyst to the mass of total solids contained in the photocatalyst paint.

[0055] Each paint was prepared by the method described below. [Preparation of paint (A-1)] According to the compounding amounts in Table 1, 1,2-bis(triethoxysilyl)ethane (binder (1)), which is the raw material of 1,2-bis(trihydroxysilyl)ethane, pure water, and the 20 wt % photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass %) prepared above were mixed to obtain 100 g of paint (A-1) with a total solids concentration of 5.5 mass %.

[0056] [Preparation of paint (A-2)] According to the compounding amounts in Table 1, 1,2-bis(triethoxysilyl)ethane (binder (1)), which is the raw material of 1,2-bis(trihydroxysilyl)ethane, pure water, and the 20 wt % photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass %) prepared above were mixed to obtain 100 g of paint (A-2) with a total solids concentration of 6.7 mass %.

[0057] [Preparation of paint (A-3)] According to the compounding amounts in Table 1, 1,2-bis(triethoxysilyl)ethane (binder (1)), which is the raw material of 1,2-bis(trihydroxysilyl)ethane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (A-3) with a total solids concentration of 10.0 mass%.

[0058] [Preparation of paint (A-4)] According to the formulations in Table 1, 1,2-bis(trimethoxysilyl)hexane (binder (2)), which is the raw material for 1,2-bis(trihydroxysilyl)hexane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (A-4) with a total solids concentration of 5.5 mass%.

[0059] [Preparation of paint (A-5)] According to the formulations in Table 1, 1,2-bis(trihydroxysilyl)octane (binder (3)), a raw material for 1,2-bis(trihydroxysilyl)octane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (A-5) with a total solids concentration of 5.5 mass%.

[0060] [Preparation of paint (A-6)] According to the compounding amounts in Table 1, 1,2-bis(trihydroxysilyl)ethane (binder (1)), which is a raw material for 1,2-bis(trihydroxysilyl)ethane, 3-methacryloxypropyltriethoxysilane (binder (4)), which is a raw material for 3-methacryloxypropyltrihydroxysilane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (A-6) having a total solids concentration of 5.5 mass%.

[0061] [Preparation of paint (A-7)] According to the blending amounts in Table 1, 1,2-bis(trihydroxysilyl)ethane (binder (1)), which is a raw material for 1,2-bis(trihydroxysilyl)ethane, 3-methacryloxypropyltriethoxysilane (binder (4)), which is a raw material for 3-methacryloxypropyltrihydroxysilane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (A-7) having a total solids concentration of 6.7 mass%.

[0062] [Preparation of paint (A-8)] According to the compounding amounts in Table 1, 1,2-bis(trihydroxysilyl)ethane (binder (1)), which is a raw material for 1,2-bis(trihydroxysilyl)ethane, 3-methacryloxypropyltriethoxysilane (binder (4)), which is a raw material for 3-methacryloxypropyltrihydroxysilane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (A-8) having a total solids concentration of 10.0 mass%.

[0063] [Preparation of Paint (A-9)] According to the compounding amounts in Table 1, 1,2-bis(triethoxysilyl)ethane (binder (1)), which is the raw material of 1,2-bis(trihydroxysilyl)ethane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (A-9) with a total solids concentration of 5.1 mass%.

[0064] [Preparation of paint (B-1)] According to the blending amounts in Table 1, pure water and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (B-1) with a total solid concentration of 5.0 mass%. Paint (B-1) does not contain a binder.

[0065] [Preparation of paint (B-2)] According to the compounding amounts in Table 1, 1,2-bis(triethoxysilyl)ethane (binder (1)), which is the raw material of 1,2-bis(trihydroxysilyl)ethane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (B-2) with a total solids concentration of 12.5 mass%.

[0066] [Preparation of paint (B-3)] According to the formulations in Table 1, 1,2-bis(trimethoxysilyl)hexane (binder (2)), the raw material of 1,2-bis(trihydroxysilyl)hexane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (B-3) with a total solids concentration of 12.5 mass%.

[0067] [Preparation of paint (B-4)] According to the compounding amounts in Table 1, 1,2-bis(trihydroxysilyl)octane (binder (3)), which is the raw material for 1,2-bis(trihydroxysilyl)octane, pure water, and the 20 wt% photocatalyst dispersion liquid (content of platinum-supported tungsten oxide particles: 20 mass%) prepared above were mixed to obtain 100 g of paint (B-4) with a total solids concentration of 12.5 mass%.

[0068] <Evaluation method and results> [Preparation of photocatalyst for evaluation] Using the photocatalytic paints (A-1) to (A-9) and (B-1) to (B-4), photocatalysts for evaluation (A-1) to (A-9) and (B-1) to (B-4) having a photocatalyst layer on a substrate were prepared. Two types of substrates, substrate (1) and substrate (2) shown below, were used as substrates for preparing the photocatalysts for evaluation. Substrate (1): Non-alkali glass (50 mm long x 50 mm wide, 0.5 mm thick) Substrate (2): Tile (Ecocarat Fine Base Simple, manufactured by LIXIL Corporation) In the water resistance test and durability test, a photocatalyst for evaluation having a photocatalyst layer on a substrate (1) was used, and in the methylene blue decomposition test, a photocatalyst for evaluation having a photocatalyst layer on a substrate (2) was used.

[0069] First, the substrate was irradiated with ultraviolet light for 30 minutes (UV ozone cleaning treatment) using an ultraviolet ozone irradiation device equipped with a low-pressure mercury lamp (manufactured by Technovision, model: UV-312). In this way, the surface of the substrate was modified to be hydrophilic. Next, the weight of the photocatalyst layer per unit area was adjusted to 5.0 g / m2. 2 The photocatalyst coating was applied to the substrate multiple times using a trigger spray to form a coating layer, and the coating layer was dried at 100° C. for 1 hour to form a photocatalyst layer. In this way, a photocatalyst body for evaluation having a photocatalyst layer on the substrate was obtained.

[0070] [Water resistance test] The water resistance test was carried out on the evaluation photocatalysts (A-1) to (A-9) and (B-1) to (B-4) having a photocatalyst layer on the substrate (1) by the method described below. In detail, 100 mL of water was poured into a glass container having a capacity of 500 mL, and the evaluation photocatalyst having a photocatalyst layer on the substrate (1) was immersed in the water. The evaluation photocatalyst was left to stand for 24 hours at a water temperature of 20°C while immersed in water. After removing the evaluation photocatalyst from the water, the evaluation photocatalyst was dried at 100°C for 24 hours, and the mass of the evaluation photocatalyst was measured.

[0071] The mass of the part (peeled part) peeled off (or detached) from the photocatalyst layer by immersing the photocatalyst in water was calculated from the difference between the mass of the photocatalyst before immersion in water and the mass of the photocatalyst after removal from water and drying. The peeling rate (unit: mass%) was calculated using the formula: "peeling rate = 100 x mass of peeled part / mass of photocatalyst layer before water resistance test". The water resistance of the photocatalyst was evaluated from the calculated peeling rate according to the following criteria. Photocatalysts for evaluation with a peeling rate of 0% or more and less than 10% were rated as "good", and photocatalysts for evaluation with a peeling rate of 10% or more were rated as "poor (NG)". Table 2 shows the peeling rates and evaluation results of the evaluation photocatalysts (A-1) to (A-9) and (B-1) to (B-4) having a photocatalyst layer on the substrate (1).

[0072] [Table 2]

[0073] Since the photocatalytic paint (B-1) does not contain a binder, it is believed that the water resistance of the evaluation photocatalytic body (B-1) was rated as "poor." The water resistance of the photocatalysts (A-1) to (A-9) and (B-2) to (B-4) for evaluation was evaluated as "good." This shows that the water resistance of the photocatalyst layer can be improved by including the binder in the photocatalyst coating material and the photocatalyst layer.

[0074] [Durability test] The durability test of the evaluation photocatalysts (A-1) to (A-9) and (B-1) to (B-4) after the water resistance test was carried out by the method shown below. The evaluation photocatalysts after the water resistance test were dried at 40°C for 24 hours. After drying, four mending tapes (a tape cut into a size of 50 mm in length and 12 mm in width from "Model No. 810-3-12" manufactured by 3M Japan Ltd.) were attached in parallel to the surface of the photocatalyst layer of the evaluation photocatalyst. Next, the four mending tapes were peeled off from the surface of the photocatalyst layer. The adhesive surfaces of the four peeled off mending tapes were visually observed to confirm the presence or absence of adhesion of the peeled off photocatalyst layer. Based on this observation, the durability of the evaluation photocatalysts (A-1) to (A-9) and (B-1) to (B-4) was evaluated.

[0075] The evaluation of the durability of the photocatalysts for evaluation (A-1) to (A-9) and (B-1) to (B-4) is shown in Table 2. The evaluation criteria for durability are as follows. Evaluation A (good): No peeled photocatalyst layer was observed adhering to any of the four mending tapes. Evaluation B (Fair): Peeled off photocatalyst layer was observed adhering to one of the four mending tapes. Evaluation C (poor): Peeled off photocatalyst layer was observed adhering to two or more of the four mending tapes.

[0076] Since the photocatalytic paint (B-1) does not contain a binder, it is believed that the durability evaluation of the photocatalytic body (B-1) for evaluation was "poor." The durability evaluation of the photocatalysts (A-1) to (A-9) and (B-2) to (B-4) for evaluation was "good" or "fair." Therefore, it was found that the durability of the photocatalyst layer can be improved by including the above-mentioned binder in the photocatalyst coating material and the photocatalyst layer.

[0077] [Methylene blue decomposition test] Using the method described below, a methylene blue decomposition test (measurement of the methylene blue fading rate), which is a confirmation test of photocatalytic activity, was conducted using the photocatalysts (A-1) to (A-9) and (B-1) to (B-4) for evaluation, which had a photocatalyst layer on a substrate (2). Specifically, 20 μL of a methylene blue aqueous solution with a concentration of 100 μmol / L was dropped onto the photocatalyst layer of the photocatalyst for evaluation using a micropipette. The photocatalyst for evaluation after dropping was dried at room temperature. Next, an ultraviolet lamp was used to measure the emission peak at 365 nm and the irradiance at 2.5 mW / cm. 2 The photocatalyst for evaluation was continuously irradiated with ultraviolet light of 100 nm for 24 hours. The reflection density of methylene blue dropped onto the photocatalyst layer of the photocatalyst for evaluation was measured to calculate the fading rate. Specifically, a black and white reflection densitometer (Ihara Electronics Co., Ltd., "R700") was used to measure the reflection density of methylene blue on the photocatalyst layer, and the fading rate of methylene blue was calculated by determining the difference δd in reflectance (unit: %).

[0078] The fading of methylene blue is caused by the photodecomposition of methylene blue dropped onto the photocatalyst layer of the photocatalyst for evaluation. The smaller the reflectance difference δd, which indicates the fading rate of methylene blue, the better the methylene blue decomposition activity of the photocatalyst layer formed by the paint.

[0079] The methylene blue fading rate measured for the evaluation photocatalysts (A-1) to (A-9) and (B-1) to (B-4) using substrate (2) and the evaluation results of the methylene blue decomposition activity of each evaluation photocatalyst are shown in Table 2. The evaluation criteria for the methylene blue decomposition test are shown below. Good: The reflectance difference δd is less than 20%. Pass: The reflectance difference Δd is 20% or more and less than 50%. Poor (NG): The reflectance difference δd is 50% or more and 100% or less.

[0080] The results of the overall evaluation of the photocatalysts for evaluation (A-1) to (A-9) and (B-1) to (B-4) are shown in Table 2. The evaluation criteria for the overall evaluation are shown below. Good: No poor (NG) ratings were recorded in the water resistance test, durability test, or methylene blue decomposition test. Poor: There is at least one poor (NG) rating in the water resistance test, durability test, and methylene blue decomposition test.

[0081] The evaluation of the methylene blue decomposition activity of the photocatalyst for evaluation (B-1) was "good." It is believed that the high evaluation of the methylene blue decomposition activity was due to the fact that the photocatalyst layer of the paint (B-1) and the photocatalyst for evaluation (B-1) do not contain a binder. However, the water resistance and durability evaluations of the photocatalyst for evaluation (B-1) were "poor," so the overall evaluation of the photocatalyst for evaluation (B-1) was "poor." The evaluation of the methylene blue decomposition activity of the photocatalysts for evaluation (B-2) to (B-4) was "poor." The photocatalyst layer of the photocatalysts for evaluation (B-2) to (B-4) contains 60 wt% of binder, so it is believed that the photocatalyst is buried in the binder, resulting in a low evaluation of the methylene blue decomposition activity. In addition, the overall evaluation of the photocatalysts for evaluation (B-2) to (B-4) was "poor."

[0082] The evaluation of the methylene blue decomposition activity of the photocatalysts for evaluation (A-1) to (A-9) was "good" or "fair." The water resistance of the photocatalysts for evaluation (A-1) to (A-9) was also "good," and the durability of the photocatalysts for evaluation (A-1) to (A-9) was "good" or "fair." Therefore, the overall evaluation of the photocatalysts for evaluation (A-1) to (A-9) was "good," and it was found that these photocatalysts for evaluation have excellent water resistance and durability, as well as high methylene blue decomposition activity. [Explanation of symbols]

[0083] 2: Photocatalyst paint 3: Base material 4: Coating layer 5: Photocatalyst layer 10: Photocatalyst coated body

Claims

1. The photocatalyst particles include tungsten oxide, a first binder, and water. The first binder has the chemical formula: (HO) 3 Si-(CH 2 ) n -Si(OH) 3 The photocatalytic paint is a 1,2-bis(trihydroxysilyl)alkane represented by the formula:

2. 2. The photocatalytic coating according to claim 1, wherein the content of the photocatalytic particles is 50% by mass or more and 99% by mass or less, when the mass of the total solid content contained in the photocatalytic coating is taken as 100% by mass.

3. 3. The photocatalytic coating according to claim 1, wherein the content of the first binder is 1% by mass or more and 50% by mass or less, when the mass of the total solid content contained in the photocatalytic coating is taken as 100% by mass.

4. 3. The photocatalytic coating material according to claim 1, wherein the first binder is a 1,2-bis(trihydroxysilyl)alkane having a carbon atom number n of 2 to 8.

5. Further comprising a second binder, 3. The photocatalytic coating material according to claim 1, wherein the second binder is a compound containing a hydroxysilyl group.

6. 6. The photocatalytic coating material according to claim 5, wherein the second binder is a compound containing a methacryloxy group.

7. The photocatalytic paint according to claim 5, wherein the sum of the content of the first binder and the content of the second binder is 1 mass% or more and 50 mass% or less when the mass of the total solids contained in the photocatalytic paint is 100 mass%.

8. Further containing a preservative component, 3. The photocatalytic coating material according to claim 1, wherein the preservative component is ethanol.

9. 3. The photocatalytic paint according to claim 1, wherein the photocatalytic paint is a suspension containing a first binder, the photocatalytic particles, and water.

10. A substrate and a photocatalyst layer provided on the substrate, The photocatalyst layer comprises photocatalyst particles and a photocatalyst having the chemical formula: (HO) 3 Si-(CH 2 ) n -Si(OH) 3 and a siloxane compound containing a dehydration condensate of 1,2-bis(trihydroxysilyl)alkane represented by the following formula:

11. A step of applying the photocatalytic coating material according to claim 1 or 2 onto a substrate to form a coating layer; and drying the coating layer.

Citation Information

Patent Citations

  • Photocatalyst coating

    WO2011059101A1